The current physical activity in persons with disability in Qatar: a cross-sectional study - Pandiyan, Uma; Kariyathankavil, Ibin; Rebbouh, Abderrahmane; EP Grami, Leila Khairallah; Thomas, Asha Susan; Sathian, Brijesh (Frontiers in Sports and Active Living, 2024)
Purpose The primary objective of this study was to measure and quantify the current level of physical activity among persons with disability in Qatar. The secondary objective was to assess and analyze the duration of sedentary behavior among individuals with disability in Qatar. Methods This was a cross-sectional epidemiological study of persons with disability living in Qatar. The study period was from October 2020 to December 2021 Results 96 persons with disabilities participated in this study. They included individuals with amputations, spinal cord injuries, cerebral palsy, and other developmental impairments. Of the respondents, 56% were male and 64% were Qataris. Of the respondents, 61.5%said that they felt psychologically and emotionally better when engaging in physical activity, and this difference was statistically significant. 71% of all those who reported feeling physically good after sport, 65% said that they enjoyed the social aspects of sports. This corroborates the beneficial effects of exercise, sports, and physical activity in persons with all types of disabilities. Conclusion There was a definite impact on the emotional and physical well-being of those who participated in the physical activities. There was less participation in team activities and two-thirds preferred to exercise alone. However, their numbers were not statistically significant because of low enrollment in the study.